Application of an automatic audiometer in the measurement of the directional characteristic of hearing - Jan ŻERA; Tomira BOEHM; Tomasz ŁĘTOWSKI (Archives of Acoustics)
This paper describes a new version of the automatic audiometer with electronic level control, adopted for the measurement of the directional characteristic of hearing. It also presents the results of the preliminary investigations of the directionality of hearing under the conditions of the threshold stimulation by a tone and by narrow-band noise.